2017
DOI: 10.1111/ibi.12502
|View full text |Cite
|
Sign up to set email alerts
|

Sooty FalconFalco concolorreproduction and population dynamics on the islands in the Sea of Oman

Abstract: Knowledge of demographic parameters affecting population dynamics is critical to the formulation of effective conservation strategies. Sooty Falcon Falco concolor is a little‐studied, Near‐threatened species; estimates of global population size and trend for this species are uncertain. They lay eggs during mid‐summer and sometimes nest in colonies. This unusual breeding ecology suggests that demographic parameters driving their population growth rate may differ from those of most other falcons. We studied Soot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The decline in the presence of breeding pairs in the study area since 2007 (and probably since 1978) is consistent with indications of decline from other studies (McGrady et al . , ) and with the view that the Sooty Falcon is suffering an ongoing, slow to moderate population decline globally (BirdLife International ). Our preliminary analyses revealed that Sooty Falcon population decline became even steeper when we accounted for temporal autocorrelation, suggesting that the population decline is real and not a consequence of temporal autocorrelation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The decline in the presence of breeding pairs in the study area since 2007 (and probably since 1978) is consistent with indications of decline from other studies (McGrady et al . , ) and with the view that the Sooty Falcon is suffering an ongoing, slow to moderate population decline globally (BirdLife International ). Our preliminary analyses revealed that Sooty Falcon population decline became even steeper when we accounted for temporal autocorrelation, suggesting that the population decline is real and not a consequence of temporal autocorrelation.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the difficulty of landing on some islands protected them from human interference, it may be that declines on inaccessible islands that occurred during our study reflect range‐wide population declines (BirdLife International ) and the inter‐related effects of lower survival and lower recruitment in the Oman population (McGrady et al . , ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations